Global Encyclopaedia of Informality, Volume 2 : Understanding Social and Cultural Complexity - Bailey, Anna (UCL Press, 2018)
Expertly practised by insiders but often hidden from outsiders, informal practices are, as this book shows, deeply rooted all over the world, yet underestimated in policy. Entries from the five continents presented in this volume are samples of the truly global collection, made possible bythe collaboration of over 200 interdisciplinary scholars.